Plagiarism among Journalism Students as a Predictor of Unethical Professional Practices: An Exploratory Case Study of Uganda, Rwanda and South Sudan - Jjuuko, Margaret (The Journal of Development Communication, 2017)
This article discusses the challenges of teaching journalism ethics in East Africa, both in journalism schools and on the job in newsrooms. It specifically explores academic plagiarism among journalism students and working journalists using Rwanda, Uganda and South Sudan as case studies. The discussion mainly draws on the authors’ experiences as journalism and media studies educators in East Africa and elsewhere in the world. The authors perceive plagiarism among East African journalism students and, to some extent working journalists, as a possible gateway to unethical behaviours during professional practice. From this perspective, plagiarism as a relatively minor form of ‘corruption’ can degenerate into an ‘accepted normalised practice’ where journalists are willing to compromise traditional journalistic values of objectivity and social responsibility to media audiences and society as a whole. From the perspective of journalism as a tool for national development, it is evident that plagiarism among journalism students, when viewed as a low level form of corruption, could influence later unprofessional journalism practices such as “envelope journalism”.
Keywords: Plagiarism; Journalism Students; Professional Practices